The Effect of Streamer Intimacy On Impulse Buying Behavior: The Mediating Role of Fear Of Missing Out Among Indonesian Live Streaming Commerce Users - Astika Ulfah Izzati; Andriansyah Bari; Frianka Anindea; Rizal Afif Abdullah Napitupulu; Nabila Nur Aisyah; Fairuz Thansril Wijaya; Joslin Putri Sarjono (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
Live streaming commerce has experienced rapid growth in Indonesia, creating new forms of consumer engagement that may encourage impulse buying. Among the psychological mechanisms frequently discussed are parasocial interaction, which reflects consumers’ perceived closeness with streamers, and fear of missing out (FoMO). Although previous studies have examined these constructs, findings regarding the mediating role of FoMO remain inconsistent, particularly in the context of Indonesian live streaming commerce. This study investigates the relationships among parasocial interaction, FoMO, and impulse buying, with a particular focus on the mediating role of FoMO. A quantitative cross-sectional design was employed using data collected from 318 active live streaming commerce users in Indonesia through an online survey. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that parasocial interaction significantly increases FoMO and directly influences impulse buying, while FoMO also positively contributes to impulse buying. In addition, FoMO partially mediates the relationship between parasocial interaction and impulse buying, suggesting that consumers’ emotional responses to missing limited opportunities reinforce the effect of streamer–consumer relationships on purchasing decisions. Rather than proposing a completely new mechanism, this study extends previous research by providing empirical evidence that supports the sequential relationship between parasocial interaction, FoMO, and impulse buying within the Indonesian live streaming commerce context, where such evidence remains limited. The findings offer practical implications for MSMEs and content creators in developing ethical engagement strategies that strengthen consumer relationships while encouraging responsible purchase decisions.